Cross-Border Consumer Resolution through TikTok: A Legal Perspective on Consumer Protection in Indonesia - Radea Respati Paramudhita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid emergence of TikTok as a digital marketplace has transformed the landscape of cross-border e-commerce. Originally functioning as a social media application, TikTok now facilitates direct commercial transactions between sellers and consumers across national borders, particularly in Southeast Asia. This shift raises significant legal concerns regarding consumer protection, jurisdictional reach, and dispute resolution. Legal systems, especially in developing countries like Indonesia, are often unprepared to address the complexity of disputes arising from such cross-jurisdictional interactions. This study, through a normative juridical approach and literature-based analysis, evaluates the limitations of Indonesia’s current legal regime in ensuring effective consumer protection in the digital trade context. The discussion emphasizes the necessity of strengthening Online Dispute Resolution (ODR) mechanisms and fostering international regulatory harmonization. Recommendations are proposed to address legislative gaps and institutional weaknesses in anticipation of the growing role of global e-commerce platforms in shaping consumer transactions.